The study of project management practices to enhance the project success / Adibah Alya Shahari - Adibah Alya, Shahari (2022)
Project Management can be described as the application of a certain guideline to the process of completing the project. It is the function of specific knowledge, suitable tools and techniques, and excellent skills to meet the objective and requirements of the Project Management (Rozenes, 2011). Successful projects created various definitions from a different views, as it can be a perception from sponsors, project managers, and system analysts (Shokri-Ghasabeh & Kavousi-Chabok, 2009). Factors that contribute to a project failure may be varies and complex to understand. Previous research studies by Kaming et al. (1997) and Noor et al. (2020) shows the biggest challenges in managing the housing project was mainly due to incompetent project manager and inexperienced project management team such as contractors and consultants. The objective of this study is to assess the implementation of project management practices in Malaysia, to evaluate the impact of project management practices on the project and to recommend the best practice for the project manager in managing the project. To have a better understanding of the project management practices, this study has referred to the Project Management Body of Knowledge (PMBOK) guide with the support from the previous research studies. This study is conducted based on samples selected i.e., housing development located at Klang Valley area. From the data collected and case studies explored, the most contributing factors in project failure are due to poor Project Schedule Management, Project Cost Management, Project Communication Management and Project Quality Management. Furthermore, it summarised the common issues for all projects selected are the project progress which all projects are delayed for more than 90 days, poor contractors’ performance in terms of financial and quality, and internal management control where iv the internal project team did not have enough knowledge to implement the best practice of project management. Therefore, PMBOK guidelines are proven to be the most effective way in promoting successful project management. Even though failure in project management practices does not mean the project itself is failed, it is proven that implementing proper project management practices helps in increasing the project success.